Pagan Leaders and Clergy: A Quantitative Exploration - Reece, Gwendolyn (Pomegranate, 2017)
This quantitative study, based on data from a large-scale national survey of Pagans, Witches and Heathens in the United States (N=3318), compares Pagan leaders and clergy to those who do not hold a formal leadership position in a group. This statistical snapshot includes demographics, characteristics of leaders as Pagans,religious practices, and participation in the larger Pagan communities. Pagan leaders are older, more educated, and have higher household incomes than non-leaders. Although there are more female than male leaders, males are statistically overrepresented in leadership. Leadership is almost all voluntary, and leaders are more likely to make lifestyle choices that emphasize commitment to Paganism. Leaders are more likely to have been formally initiated, have more years of experience in Paganism, and rank themselves as more advanced than non-leaders. They exhibit expertise typically associated with clergy in mainstream religions, and they participate in specialized magickal practices at higher rates than non-leaders. Leaders and clergy are not only more involved in their groups in which they have formal leadership, but also participate in activities as part of the larger “Pagan community” at a higher degree of frequency and take advantage of opportunities and resources in the broader Pagan community more than non-leaders.